2003
DOI: 10.1007/s00122-003-1361-6
|View full text |Cite
|
Sign up to set email alerts
|

An integrative genetic linkage map of winter wheat (Triticum aestivum L.)

Abstract: We constructed a genetic linkage map based on a cross between two Swiss winter wheat ( Triticum aestivum L.) varieties, Arina and Forno. Two-hundred and forty F(5) single-seed descent (SSD)-derived lines were analysed with 112 restriction fragment length polymorphism (RFLP) anonymous probes, 18 wheat cDNA clones coding for putative stress or defence-related proteins and 179 simple-sequence repeat (SSR) primer-pairs. The 309 markers revealed 396 segregating loci. Linkage analysis defined 27 linkage groups that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(128 citation statements)
references
References 44 publications
(51 reference statements)
5
121
1
Order By: Relevance
“…Therefore, it is reasonable to assume that QSnl04.daw-1B and QSnl05.daw-1B are different from those previously reported on 1BS (13,16,17) based on comparative chromosomal map position for markers associated with QTL. If toxin insensitivity is associated with QTL on 1BS in this study, then a gene or genes (1,21) but the lack of common markers between genetic maps did not allow unambiguous co-location for seedling and flag leaf resistance at this locus. It was expected that QSnl04.daw-2A and QSnl05.daw-2A would reside in the same marker interval; however, analysis using data from successive years showed overlapping QTL.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, it is reasonable to assume that QSnl04.daw-1B and QSnl05.daw-1B are different from those previously reported on 1BS (13,16,17) based on comparative chromosomal map position for markers associated with QTL. If toxin insensitivity is associated with QTL on 1BS in this study, then a gene or genes (1,21) but the lack of common markers between genetic maps did not allow unambiguous co-location for seedling and flag leaf resistance at this locus. It was expected that QSnl04.daw-2A and QSnl05.daw-2A would reside in the same marker interval; however, analysis using data from successive years showed overlapping QTL.…”
Section: Discussionmentioning
confidence: 80%
“…A total of 25 (4.8 %) skewed markers (0.01 P < 0.05) were distributed on nine different LGs, ranging from zero to six for each group. Three segregation distortion regions, defined as regions with three or more closely linked markers exhibiting significant segregation distortion (Paillard et al 2003), were found on LG3, LG6 and LG7. MAT-A and MAT-B were mapped, respectively, on LG4 and LG11.…”
Section: Linkage Analysis and Mappingmentioning
confidence: 99%
“…A genetic linkage map based on microsatellite (SSR) and restriction fragment length polymorphism (RFLP) markers was established (Paillard et al 2003). Three hundred and ninety four loci (186 RFLPs and 208 SSRs) were used on the 'Arina Forno' genetic linkage map, and by linkage analysis 380 of these loci mapped to 27 linkage groups with an average marker density of around 8 cM and spanning a total of 3,086 cM.…”
Section: Genetic Linkage Mapmentioning
confidence: 99%